Pemanfaatan Media Smart Board Untuk Meningkatkan Kemampuan Membaca Huruf Hijaiyah Anak Usia 5-6 Tahun Di KB Ar-Rohmah I Singosari - Choiro Umatin; Mochammad Ramli Akbar; Henni Anggraini (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
Basic education plays a crucial role in providing students with basic knowledge and skills, including reading skills as a foundation for subsequent learning. Early reading skills, particularly reading the hijaiyah letters, require serious attention because they impact advanced reading skills. Initial observations in class B of KB Ar-Rohmah I Singosari showed that most children aged 5–6 years were unfamiliar with the hijaiyah letters and experienced reading difficulties, resulting in suboptimal learning activities. This situation necessitates the use of engaging learning media that are appropriate to the characteristics of early childhood. This study aims to determine the use of smartboards and their impact on the hijaiyah reading skills of 5–6-year-old children at KB Ar-Rohmah I Singosari. This study used the Classroom Action Research (CAR) method, implemented in two cycles, each consisting of planning, implementation, observation, and reflection. Smartboards were used to visually and interactively display the Hijaiyah letters to help children recognize and read them more easily. The results showed that: the use of smartboards in teaching the Hijaiyah letters at KB Ar-Rohmah I Singosari was implemented through lesson planning, visual and audio presentation of the Hijaiyah letters, teacher pronunciation demonstrations, interactive reading activities, and evaluation of children's development. The use of smartboards proved effective in improving the reading skills of children aged 5–6 years. Improvements were seen in letter recognition, pronunciation accuracy, reading fluency, and self-confidence. In Cycle I, children's reading skills began to improve, while in Cycle II, the improvement became more significant and stable, thus achieving the research success indicator.